Effects of electric field on the thermal diffusivity of conductors in three-layer solid configurations - Jibrin, Sani (2015)
In order to extract the thermal properties of thin films from their thermal responses an analytical model is developed by solving the heat diffusion equation. In this study, a novel mathematical theory essential for the experimental determination of thermal diffusivity of conductors in three-layer solid configurations by the Converging Thermal Wave Technique is developed. This is achieved by expressing the hyperbolic Laplace associated solution of the derived equation in negative exponential form. Binomial series expansion is then used to simplify the solution and hence, Laplace conversion tables, in place of the tedious integral inversion technique are finally used to retrieve the temporal temperature profile for the three-layer solid sample in real space and time domains. The equation is plotted using Mathematica Software and its accuracy is checked by performing sensitivity analysis on all the physical parameters contained in the derived equation. The result of the sensitivity analysis shows that the mathematical model is sensitive to all relevant parameters needed for the evaluation of the thermal diffusivity of the sample. Using the Converging Thermal Wave Technique, three different sets of thermal diffusivity experiments are performed on previously prepared samples. The first set of experiment comprising four three-layer samples is performed to test the mathematical theory and calibrate the measuring scheme and apparatuses. Results obtained in this series of experiments show that the mathematical model and the measuring scheme adopted for the thermal diffusivity evaluation of the samples are accurate to within about 5% error.The second set of experiments were performed on different three-layer solid samples when direct electric current pass across the samples. Results obtained here indicate that the thermal diffusivity value of the metal foils in three-layer solid configurations increase with the potential difference applied across the metal foils. It is also observed in this series of experiments that the temperature of the metal foils increases slightly as a result of the Joule heating effects. When different three-layer solids are placed in a uniform static electric field and are being charged either positive or negative as the PD is varied from 1.00 V to 10.00 V in a step of 1 V each, the effect of electrostatic field on the thermal diffusivity of metal is investigated. At both positive and negative static charge on the sample, ten different temperature signal readings are obtained as the potential difference of the DC power source is varied. In this way, the free electrons in the conductor are made to move either towards or away from the temperature signal detection point respectively and hence the effect of the flow of free electrons in an open circuitry is established. It is found out that free electrons flowing both normal and parallel to thermal dissipation path in a metal affect its thermal diffusivity significantly. When electrons flow towards the thermal dissipation path due to electrostatic repulsion, the thermal diffusivity value of the metal is observed to increase and when the direction of electrons flow and thermal dissipation path due to electrostatic attraction are opposite one another, the thermal diffusivity value for the sample decreases. The last phenomenon is understood to be the results of the fact that electrons in a metal behave like a collection of gas particles, ’Fermi-Gas’ such that they move about through the metal unhindered and unaffected by the potentials of the ion core and hence remained un scattered for quite a long time. Within the limit of the room temperature at which the experiment is carried out, scattering of electrons in the metal by phonons is negligible. Similarly, for metals free from point defects, impurity and imperfections scattering by point defects and crystal imperfection is also ruled out. Hence, the applied potential difference accelerates the electrons towards or away from the temperature probe. When the electrons move towards the probe the thermal diffusivity value for the metal increases, and decrease when the electrons flow in the opposite direction. We also note that all these happened with no additional heat in the solid as the phenomenon occur in an open circuitry such that the Joule heating effects of flowing electrons are eliminated.